Pipeline disinfection device - WANG DINGLEI; ZHANG XINGZI; QIN LONG; CHEN LAILI; YANG DAOGUI; LI JIANHAO; XIONG LEI; CAO ANXIONG (2025)
The utility model belongs to the technical field of sewage disinfection, and particularly relates to a pipeline disinfection device which comprises a sewage pipe and a disinfection device body arranged on the sewage pipe, the sewage pipe is made of transparent materials, and the disinfection device body comprises an ultraviolet lamp and a supporting assembly which are arranged on the surface of the sewage pipe in a sleeved mode. The supporting assembly comprises a supporting ring I and a supporting ring II, a plurality of connecting columns are arranged between the supporting ring I and the supporting ring II, base plates are arranged on the two sides of each connecting column respectively, and the ultraviolet lamps are detachably arranged between the adjacent connecting columns and supported through the base plates. The supporting ring I, the supporting ring II, the connecting column and the sleeve form a cavity for containing the ultraviolet lamp, the two sides of the ultraviolet lamp are placed on the base